Postoperative Intracranial Hypotension-Associated Venous Congestion after Spinal Surgery Managed with Multiple Blood Patches: Case Report - Kurzbuch, Arthur Robert; Bourlond, Baudouin; García Martínez, Juan José; Bonjour, Thierry; Novaes, Natalia P.; Tuleasca, Constantin; Millán, Diego San (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background Postoperative intracranial hypotension-associated venous congestion (PIHV) is a rare event. The authors report the case of a patient presenting with PIHV after spinal surgery following the sudden loss of cerebrospinal fluid (CSF) induced by suction drainage.Methods A 69-year-old patient underwent uneventful revision surgery for wound dehiscence after lumbar surgery with placement of a subfascial suction drain.Results Postoperatively, the patient presented with fluctuating consciousness and a generalized tonic–clonic seizure. Computed tomography (CT) and serial magnetic resonance imaging (MRI) were performed showing convexity subarachnoid hemorrhages (SAHs), diffuse swelling of the brain and thalami and striatum bilaterally without diffusion restriction, and signs of intracranial hypertension resulting in pseudohypoxic brain swelling in PIHV. A dural leak at L3–L4 was treated with several CT-guided patches combining autologous blood and fibrin glue injections. The patient recovered without neurologic deficit and follow-up MRI revealed progressive complete reversal of brain swelling, and re-expansion of CSF spaces.Conclusion PIHV is a rare but potentially fatal entity. Awareness of PIHV after cranial or spinal surgery leads to early treatment of CSF hypovolemia and possibly better clinical outcome. Following acute CSF volume loss, an acute elevation of cerebral blood volume overcoming autoregulatory mechanisms seems a likely explanation for diffuse cerebral vasogenic edema and SAH in PIHV.
Keywords: CSF loss; hypoxic brain swelling; intracranial hypotension; postoperative intracranial hypotension-associated venous congestion; suction drain